Reliability and validity of the 21-m shuttle-run test and its application to youth soccer players during the preseason training - Byun, K. (Physical Activity and Nutrition, 2023)
[Purpose] This study has two purposes: first to assess the reliability and validity of the 21-m shuttle-run test (21-m SRT) and, second, to evaluate the practicality of the 21-m SRT for youth soccer players during preseason training. [Methods] Twenty-seven youth soccer players (15.9 ± 0.7 yrs., males) participated in the present study. To assess the reliability of the test, each player performed the 21-m SRT twice, on separate days. Criterion validity of the 21-m SRT was determined by examining the relationship between directly measured V3 O2max and 21-m SRT performance. To test the practicality of the 21-m SRT, three 21-m SRTs and two graded exercise tests on a treadmill were performed by each youth soccer player during preseason training. [Results] Results revealed that the 21-m SRT has high correlation coefficients (r = 0.87) between test and retest and has moderate correlation coefficients (r = 0.465) between V3 O2max and SRT performance. As V3 O2max significantly increased after the training period, SRT performance (distance and heart rate immediately after the 67th shuttle run) also positively changed during the preseason training period. [Conclusion] The 21-m SRT has high reliability with moderate validity, and it is an effective tool for coaches to examine aerobic capacity and the efficacy of a training program for youth soccer players during the preseason training period.